Paulo Freire and Technical and Technological Professional Education (Práxis Educativa, 2020)
This article aimed to rescue and reflect on how Paulo Freire’s teachings on the ideals of a liberating, dialogical and democratic education can help to implement the assumptions of the Technical and Technological Professional Education. It was sought to discuss the fundamental concepts in the Freirian studies for the implementation of humanistic education in the interim of contemporary schools, aiming at the omnilateral education of students, so that they may be able to build their sociability as autonomous citizens and protagonists of their stories. The Freirian legacy seems extremely current due to the reality that afflicts professionals in the Brazilian education. Thus, the text discusses the assumptions of professional education in the light of the teachings of the great Brazilian educator.Keywords: Paulo Freire. Professional Education. Integral education.